Jezikoslovni in družbeni vidiki kategorije spola v slovenščini in angleščini - Šabec, Nada (Slavistična revija, 2019)
Linguistic differences between Slovene grammatical and English semantic gender have implications for the differences in which the two languages address the broader sociocultural issue of non-sexist language use (gender-specific vs. gender-neutral forms, respectively). Problematic areas associated with non-sexist language use are discussed, and measures promoting gender-sensitive language use and awareness of it are presented and critically evaluated.
Keywords: angleščina; English language; grammatical gender; jezikovni seksizem; linguistic sexism; semantic gender; semantični spol; Slovene language; slovenščina; slovnični spol